The Influence of COVID-19 on Economics in Indonesian Healthcare and Finance - Hariyanto, Eko; Pandansari, Tiara; Wakhudin, Wakhudin (International Journal Labs, 2023)
This research is a research with event study method. The events observed are events that are affected by the Covid-19 epidemic. There are 3 events that will be examined in this study, namely the announcement of the covid-19 epidemic by WHO, which means including in Indonesia on March 11, 2020. The second event is the implementation of the PSBB for the first time in Indonesia, namely in the Capital Region of DKI Jakarta, which took effect on April 10, 2020. The third event was the announcement of OJK regulations, namely POJK Policy Number 11/POJK.02/2020 , on March 20 2020. From these events it will be associated with the economy in Indonesia, which is proxied by stock returns, because by looking at this stock return it describes the economy in a country. For this research it is only limited to the health care and financial sectors. These two sectors are considered to be the most affected by the presence of Covid-19. The methodology used in this research is the study of abnormal return testing events. The abnormal return calculation method uses the Market Model, with an estimated period of 60 days and a window period of 15 days. Testing with the average difference test before and after the event, with an error rate of 5%. The window period was taken at the start of the pandemic, then when the second period was at its peak, and when the pandemic had slumped. Differences in observations to be used as comparison material.